Protective effect of rosiglitazone against acetaminophen-induced acute liver injury is associated with down-regulation of hepatic NADPH oxidases. (4th January 2017) - Wang, Jun-Xian; Zhang, Cheng; Fu, Lin; Zhang, Da-Gang; Wang, Bi-Wei; Zhang, Zhi-Hui; Chen, Yuan-Hua; Lu, Yan; Chen, Xi; Xu, De-Xiang
Highlights: RSG pretreatment protects against APAP-induced acute liver injury. RSG pretreatment inhibits APAP-induced hepatic cell death. RSG alleviates hepatic GSH depletion during APAP-induced liver injury. RSG downregulates hepatic NADPH oxidases during APAP-induced liver injury. Synthetic PPAR-γ agonists might be effective agents for preventing liver injury. Abstract: The peroxisome proliferator-activated receptor gamma (PPAR-γ) is a ligand-activated nuclear receptor that regulates glucose and lipid metabolism. The aim of the present study was to investigate the effects of rosiglitazone (RSG), a synthetic PPAR-γ agonist, on acetaminophen (APAP)-induced acute liver injury. Male CD-1 mice were injected with APAP (300 mg/kg). Some mice were pretreated with RSG (20 mg/kg) 48, 24 and 1 h before APAP injection. As expected, RSG pretreatment alleviated APAP-induced acute liver injury. Moreover, RSG pretreatment attenuated APAP-induced hepatic cell death and improved the survival. Although it did not affect hepatic cytochrome P450 (CYP)2E1 expression, RSG pretreatment attenuated reduction of hepatic glutathione peroxidase (GSH-Px), glutathione reductase (GSH-Rd) and glutathione S-transferase (GST) activities, inhibited upregulation of hepatic nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX)-2 and NOX-4, and alleviated hepatic GSH depletion during APAP-induced acute liver injury. In addition, RSG pretreatment suppressed activation of hepatic nuclear factor kappa B (NF-κB) and extracellular signal-related kinase (ERK)/mitogen-activated protein kinase (MAPK) signaling during APAP-induced acute liver injury. These results provide a novel mechanistic explanation for RSG-mediated protection against APAP-induced acute liver injury. The present results suggest that synthetic PPAR-γ agonists might be effective agents for preventing the progression of APAP-induced acute liver injury.